2013
DOI: 10.5301/ijao.5000128
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of Extracorporeal Cytokine Removal: A Systematic Review of the Literature on Animal Experimental Studies

Abstract: Experimental animal studies indicate that HVHF (especially with HCO filters) and plasmafiltration have the potential to achieve appreciable IL-6 and IL-10 clearances. However, only PF can remove TNF-alpha reliably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
1
18
1
1
Order By: Relevance
“…We had earlier published two systematic reviews on the same topic focusing on ex-vivo cytokine removal and cytokine removal in animal studies respectively. 53,54 The findings of the human studies reported here are broadly consistent with the findings of these two previous systematic reviews.…”
Section: Relation To Previous Literaturesupporting
confidence: 90%
“…We had earlier published two systematic reviews on the same topic focusing on ex-vivo cytokine removal and cytokine removal in animal studies respectively. 53,54 The findings of the human studies reported here are broadly consistent with the findings of these two previous systematic reviews.…”
Section: Relation To Previous Literaturesupporting
confidence: 90%
“…Enhanced cytokine depletion with high cutoff filters has been reported in a number of studies in vitro and in vivo [20,21,22]. It has been proposed that the concurrent removal of multiple mediators from the circulation can contribute to restoring immune homeostasis by eliminating the peaks of cytokine blood concentrations in the early phase of sepsis (peak concentration hypothesis) [23], by effecting the depletion of cytokines due to re-equilibration of blood and tissue cytokine levels (threshold immunomodulation hypothesis) [24], by inducing increased lymphatic flow and a displacement of mediators to the blood compartment (mediator delivery hypothesis) [25], or by directly acting on inflammatory cells, such as monocytes or neutrophils (cytokinetic model) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several extracorporeal filtering techniques have been used to remove these cytokines [12, 13]. Continuous veno-venous hemofiltration (CVVH) is one of the emerging techniques that has been studied for this purpose [1417].…”
Section: Introductionmentioning
confidence: 99%